2021
DOI: 10.3390/bs11060090
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Length Expands Perceptual and Emotional Evaluations in Written Japanese Sound-Symbolic Words

Abstract: In this study, we examined whether vowel length affected the perceptual and emotional evaluations of Japanese sound-symbolic words. The perceptual and emotional features of Japanese sound-symbolic words, which included short and long vowels, were evaluated by 209 native Japanese speakers. The results showed that subjective evaluations of familiarity, visual imageability, auditory imageability, tactile imageability, emotional valence, arousal, and length were significantly higher for sound-symbolic words with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…We counterbalanced word lists of the Japanese pseudowords and spoken Japanese real words between participants to control the effects of stimuli (De Houwer et al 2001 ), such as the sound symbolic effects of stimuli, which linguistic features (e.g., spoken sounds) nonarbitrarily connect to referentially perceptual and emotional features (e.g., Ando et al 2021 ; Kambara and Umemura 2021 ; Lin et al 2021 ; Namba and Kambara 2020 ). Furthermore, to counterbalance word stimuli, we separated the samples into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…We counterbalanced word lists of the Japanese pseudowords and spoken Japanese real words between participants to control the effects of stimuli (De Houwer et al 2001 ), such as the sound symbolic effects of stimuli, which linguistic features (e.g., spoken sounds) nonarbitrarily connect to referentially perceptual and emotional features (e.g., Ando et al 2021 ; Kambara and Umemura 2021 ; Lin et al 2021 ; Namba and Kambara 2020 ). Furthermore, to counterbalance word stimuli, we separated the samples into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…The current research focuses on the difference in vowel length between Japanese short and long vowels. Long vowels are estimated to be 2,4 times lengthier than short vowels, and long vowels contain a pitch fall within a word, while short vowels do not (Lin et al, 2021). These previous studies also find that short and long vowels differ in terms of duration and pitch fall.…”
Section: Introductionmentioning
confidence: 71%
“…The meaning of a word may vary when the pitch contour is altered (1); an unaccented word does not have this high-low pitch sequence (2). Since only the first mora of a long vowel receives a high pitch when accented, the high low-pitch contour must occur within the long vowel (Lin et al, 2021). However, the pitch contour of a long vowel must be either high-high or low-high, followed by a high pitch, as demonstrated in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we did not consider sound-symbolic (non-arbitrary) effects of the associative learning for novel linguistic forms and gustatory stimuli. Previous studies on sound symbolism have reported that specific verbal sounds or oral shapes that are required to produce certain verbal sounds are associated with certain perceptual and emotional evaluations [ 39 , 40 , 41 , 42 , 47 , 48 , 49 , 50 ]. A previous study found that specific verbal sounds increased expectations of certain tastes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, each subject evaluated the candy or chocolate using each 5 point semantic differential scale. We based each semantic differential scale on other studies [ 32 , 33 , 38 , 39 , 40 , 41 , 42 ]. The 10 semantic differential scales linked with sweetness (1: not sweet; 5: sweet), hardness (1: soft; 5: hard), coolness (1: not cool; 5: cool), sourness (1: not sour; 5: sour), astringency (1: not astringent; 5: astringent), spiciness (1: not spicy; 5: spicy), familiarity (1: unfamiliar; 5: familiar), preference (1: not like; 5: like), arousal (1: calm; 5: excited), and deliciousness (1: not delicious; 5: delicious).…”
Section: Methodsmentioning
confidence: 99%